FINANCIAL MARKET’S ROLE IN DETERMINING THE VALUE OF INTERNATIONAL BUSINESS INTANGIBLE ASSETS - Kyfyak, Viktoria; Rogovska-Ishchuk, Iryna; Mykhaylyna, Diana (Baltic Journal of Economic Studies, 2024)
Abstract. With the entry of humanity into the era of digital technologies and the knowledge economy, the importance of intangible capital for the world economy and international business has been growing. In the context of forced virtual communication due to the prolonged impact of the COVID-19 pandemic and social conflicts and cyberattacks in connection with russia’s hybrid war in Ukraine, the importance of such intangible assets as reputation, investor and customer loyalty, consumer data, branding, intellectual know-how, copyright etc. have acquired a new meaning and value. The research purpose is to complement the conceptual and methodological approach to identifying the essence and value of leading international companies’ intangible assets, in particular their undisclosed part, including through financial market data. The article substantiates the assumption that the identified gap between market capitalization and shareholder equity of an individual company acts as a sought-after undiscovered part of intangible assets, which is absent in the company’s official reports and includes such components as reputation, customers’ and investors’ trust and loyalty, brand strength, etc. Given the dynamic development of the international business sphere, the critical importance of such factors as flexibility, speed in decision-making, investors need to receive the fastest and most up-to-date information about the potential of an individual company, in particular, in terms of the value of its intangible assets. Under these conditions, the approach proposed by us can serve as an effective decision-making tool and an alternative way of identifying the real value of the company’s intangible assets.
Keywords: financial market, global value chains, intangible assets, international business, multinational corporations